A non-Western adaptation of the Situated Academic Writing Self-Efficacy Scale (SAWSES) - Doenyas, Ceymi; Gul, Zeynep Tunay; Alci, Bulent (ELSEVIER SCI LTD, 2023)
A key parameter for academic and professional success is the academic writing skill, which not only involves following rules and codes but also engaging cognitive skills to satisfy complex task demands. Academic writing is challenging for most students. However, this critical skill has not been in research focus until recently, as students are inherently expected to possess it. The present study carries this research focus on the academic writing skill to a non-Western population in which strong academic competition and high stakes make this skill relevant for psychological well-being. The Situated Academic Writing Self-Efficacy Scale (Mitchell et al., 2021) was adapted to Turkish and its validity and reliability was tested in a sample of Turkish undergraduate students (n = 300, 65% females). CFA results confirmed the scale's original structure consisting of 3 dimensions (Writing Essentials, Relational-Reflective Writing, and Creative Identity) and 16 items. Cronbach's alpha of .895 revealed high internal consistency. The Turkish version of the scale, which is also its first non-Western adaptation, emerged as a reliable tool to measure situated (contextual) academic writing self-efficacy. This scale can help researchers, practitioners, teachers, and students alike determine students' perceived self-efficacy in academic writing and how this perception can be strengthened based on their total and sub-dimension scores. Thereby, this scale holds the potential to enhance this quality in low-scoring individuals, with possible benefits for their academic and professional success and psychological well-being, as well as guiding research into academic writing self-efficacy and motivation in native and foreign languages and in the world's current digital environment.
Keywords: Academic writing; Scale adaptation; Self-efficacy; University students; Writing efficacy; CROSS-CULTURAL ADAPTATION; PERCEPTIONS; TRANSLATION; VALIDATION; GUIDELINES; ISSUES; Education & Educational Research; Linguistics